EVALUATION OF THE REALIZATION OF SHIP TRIP ACHIEVEMENTS ON THE MERAK – BAKAUHENI ROUTE AT MERAK FERRY PORT BANTEN PROVINCE - Komalasari, Yeti; Febriansyah, Febriansyah; Wibisono, Yohan; Amanda, Monica; Khairani, Muhammad; Kartini, Sri; Salsabila, Salsabila (IWTJ : International Water Transport Journal, 2025)
Merak Ferry Port with the Merak – Bakauheni route located in Banten Province, operates 30 ships in March with operational hours of 24 hours/day, resulting in many trips per pier. However, the realization of trips often falls short due to several factors such as breakdowns, vehicle breakdowns, facility damage, bad weather, and ship speed being below the minimum. he existing condition of ship trips per pier resulted in a target of 153 trips, with 103 trips realized, a difference of 50 trips, and a trip percentage of 68%. The result of ship service time in the waters produced an evaluation of effective time against berth working time, with 56 points meeting the standard and 28 points not meeting the standard. The effective time against berth working time met the standard.The conformity of sailing time for executive ships was 60 minutes, and for regular ships, it was 96 minutes. The realization of sailing time was 27 trips, while the scheduled trips were 115, showing that the conformity of sailing time to the realization and scheduled trips did not meet the standard. The results of this study call for faster loading and unloading processes, more effective penalties, provision of tow trucks, heavy equipment, technicians specializing in different types of vehicles, ship performance indicators, side ramp improvements, and changes in ship operation patterns.